Improved survival and tumor control with Interleukin-2 is associated with the development of immune-related adverse events: data from the PROCLAIMSM registry. Issue 1 (19th December 2017) - Curti, Brendan; Daniels, Gregory A.; McDermott, David F.; Clark, Joseph I.; Kaufman, Howard L.; Logan, Theodore F.; Singh, Jatinder; Kaur, Meenu; Luna, Theresa L.; Gregory, Nancy; Morse, Michael A.; Wong, Michael K. K.; et al.
Abstract : Background: Immune related adverse events (irAEs) are associated with immunotherapy for cancer and while results suggest improvement in tumor control and overall survival in those experiencing irAEs, the long-term impact is debated. We evaluated irAE reports related to high dose interleukin-2 therapy (IL-2) documented in the PROCLAIM SM registry data base from 2008 to 2016 (NCT01415167, August 9, 2011). Methods: Reports on 1535 patients, including 623 with metastatic melanoma (mM) and 919 with metastatic renal cell cancer (mRCC) (7 patients had both diseases), were queried for irAEs. The timing of the event was categorized as occurring before, during or after IL-2 or related to any checkpoint inhibitor (CPI). mM patients and mRCC patients were analyzed separately. Tumor control [complete + partial response + stable disease (CR + PR + SD) was compared between those experiencing no irAE versus those with the development of irAEs. Survival was analyzed by tumor type related to timing of irAE and IL-2, and in those with or without exposure to CPI. Results: Median follow-up was 3.5+ years (range 1–8+ years), 152 irAEs were reported in 130 patients (8.4% of all PROCLAIM SM patients): 99 (16%) in mM and 53 (5.8%) in mRCC patients. 31 irAEs occurred prior to IL-2, 24 during IL-2, and 97 after IL-2 therapy. 74 irAEs were attributed to IL-2 only (during/ after IL-2). Of the 97 post IL-2 irAEs, 24 were attributed to CPI, and 15 could not be distinguished as caused by IL-2 or CPI. Tumor control was 71% for those experiencing irAE, and 56% for those with no irAE ( p = 0.0008). Overall survival was significantly greater for those experiencing irAEs during/ after IL-2 therapy, compared to those with no irAE or irAE before IL-2 therapy, in mM patients, median 48 months vs 18 months ( p < 0.0001), and in mRCC patients, median 60 months vs 40 months ( p = 0.0302), independent of CPI-related irAEs. IL-2-related irAEs were primarily vitiligo and thyroid dysfunction (70% of IL-2 related irAEs), with limited further impact. Conclusions: irAEs following IL-2 therapy are associated with improved tumor control and overall survival. IrAEs resulting from IL-2 and from CPIs are qualitatively different, and likely reflect different mechanisms of action of immune activation and response.